MORPHOMETRIC CHARACTERISTICS OF THE RAT LIVER IN NORMAL CONDITIONS AND UNDER POLYPHARMACY: EFFECTS OF TWO DIFFERENT ANTI-INFLAMMATORY DRUGS - Abduraimov Zafarjon Abduraimovich,; Alkov Ruslan Alimjonovich,; Lutfullaev Khafizullo Zaynullaevich,; Ruzikulov Xumoyunbek Kuylievich,; Yakubova Khadichakhon Kasymkhonovna, (World Scientific Research Journal, 2025)
The effectiveness of treatment in humans and the desire to eliminate all coexisting diseases often inevitably lead to the prescription of multiple drugs, which, in turn, causes polypharmacy. Polypharmacy is a serious problem in healthcare because it clinically manifests as reduced pharmacotherapy efficacy, an increased risk of adverse reactions, and a significant rise in healthcare expenditures. Although the term “polypharmacy” is widely used in the medical literature, a universally accepted definition does not exist. The present study aimed to compare morphometric parameters of the liver in normal conditions and under polypharmacy when exposed to anti-inflammatory drugs, thereby contributing additional data on morphological and morphometric alterations in hepatic tissue.